2018
DOI: 10.1080/21691401.2018.1451873
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of nano lipid formulation containing CNS acting drug: molecular docking, in-vitro assessment and bioactivity detail in rats

Abstract: The study performed molecular docking, formulated, characterized thymoquinone (TQ) loaded solid lipid nano particles (TQSLN) and exhibited comparative antidepressant activity. TQ loaded nano lipid formulations were prepared by solvent injection methods and characterize for different in-vitro parameters. The optimized formulation was evaluated for depression using unpredictable chronic mild stress (UCMS) model for a period of six weeks. TQSLN was assessed in modified forced swim test (MFST), tail suspension tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…TQ is a lipophilic compound with molecular weight of 164.2 42 , log P of 2.54 43 and a low aqueous solubility of about 500 μg/ml 44 . TQ possesses antioxidant 45,46 , anti-inflammatory 47,48 , anti-hyperlipidemic 49 , anti-depressant 50 and antimicrobial activities 51 , and its use in combination with chemotherapeutic agents reduces their side effects 52,53 . TQ possesses antiproliferative activity on various types of cancer including colorectal carcinoma 54 , and was found to induce cell cycle arrest and apoptosis in HCT-116 human colon cancer cells 55 .…”
mentioning
confidence: 99%
“…TQ is a lipophilic compound with molecular weight of 164.2 42 , log P of 2.54 43 and a low aqueous solubility of about 500 μg/ml 44 . TQ possesses antioxidant 45,46 , anti-inflammatory 47,48 , anti-hyperlipidemic 49 , anti-depressant 50 and antimicrobial activities 51 , and its use in combination with chemotherapeutic agents reduces their side effects 52,53 . TQ possesses antiproliferative activity on various types of cancer including colorectal carcinoma 54 , and was found to induce cell cycle arrest and apoptosis in HCT-116 human colon cancer cells 55 .…”
mentioning
confidence: 99%
“…As per our earlier published work, thymoquinone loaded Solid lipid nanoparticles (TQSLN) Formulation were prepared and characterized [22]. In the present study thymoquinone loaded Solid lipid nanoparticles (TQSLN) was prepared and was subjected for visual observation, particle size, zeta potential, transmission electron microscopy (TEM) and differential scanning calorimetry (DSC).…”
Section: Thymoquinone Loaded Solid Lipid Nanoparticles (Tqsln) Formulmentioning
confidence: 91%
“…Researchers have shown greater interest in the development of solid lipid nano particle (SLNs) due to their unique structure, properties and biocompatibility [21]. Recently, a formulation of thymoquinone solid lipid nanoparticle was developed to enhance the solubility and bioavailability of conventional thymoquinone suspension and studied in unpredictable chronic mild stress models of depression [22]. Thus, the purpose of the present study was to evaluate the effect of thymoquinone solid lipid nanoparticle (TQSLN) in depression model of rats and study its mechanism via indoleamine 2, 3-dioxygenase pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Alam et al [ 34 ] studied the possible effect of TQ-loaded solid lipid nano particles (TQ-SLN) on the brain, comparing it to free TQ through the determination of a modified forced swim test, tail suspension test, and locomotor activities in rats. They found that TQ-SLN increased TQ delivery to brain tissues faster than free TQ, as demonstrated by determination of 5 hydroxytryptamine, dopamine, and norepinephrine levels in the brain ( Figure 4 ).…”
Section: Biological Activities Of Thymoquinone Nanoformulationmentioning
confidence: 99%